Analisis Pengaruh Kualitas Produk dan Kualitas Layanan Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan Sebagai Variabel Intervening PT. Panasonic Padang - Muhammad Fadhil Fadhlullah; Vicky Brama Kumbara; Della Asmaria Putri (CV. ITTC INDONESIA, 2026)
This study aims to determine the extent to which Product Quality and Service Quality influence Customer Loyalty, with Customer Satisfaction serving as an intervening variable at PT Panasonic Padang. Data collection was conducted via a survey involving the distribution of questionnaires to 99 respondents. The analysis employed path analysis using the Partial Least Squares (PLS) approach via the SmartPLS software. Partial test results indicate a significant influence of Product Quality on Customer Satisfaction, whereas Service Quality does not have a significant influence on Customer Satisfaction. Furthermore, both Product Quality and Service Quality were found to have a significant influence on Customer Loyalty. Additionally, Customer Satisfaction significantly influences Customer Loyalty. Results regarding indirect effects show that Customer Satisfaction mediates the influence of Product Quality on Customer Loyalty, while the influence of Service Quality on Customer Loyalty via Customer Satisfaction was found to be insignificant (i.e., Customer Satisfaction does not mediate the influence of Service Quality on Customer Loyalty).